Deep brain stimulation lead removal in Tourette syndrome. (August 2020) - Deeb, Wissam; Leentjens, Albert F.G.; Mogilner, Alon Y.; Servello, Domenico; Meng, Fangang; Zhang, Jianguo; Galbiati, Tommaso Francesco; Okun, Michael S.
Abstract: Introduction: Tourette syndrome (TS) is a complex neuropsychiatric disorder. A small percentage of individuals with TS can experience persistent severe, refractory, and impairing tics. Deep brain stimulation (DBS) has been increasingly used for symptom management, especially in these settings. In this article, we aim to evaluate the rate and the reasons for removal of DBS hardware in TS patients. Methods: Data was analyzed from patients enrolled in the Tourette Association of America's International Tourette Syndrome Registry and Database. Results: Fifteen of 269 (5.6%) patients required removal of their DBS systems. The mean age at explantation was 33.8 years. In these cases we observed a rate of 1.9 explantations per year of follow up from implantation. None of the removals took place in the immediate post-operative period. Infection was the most common cause (46.7%). Only one patient received explantation for tic resolution. There were no significant associations between explantation and the presence of specific psychiatric comorbidities, including OCD, depression, anxiety, or ADHD. Discussion: The rate of removal of 5.6% was lower than the previously reported rate in the TS DBS literature. Infections accounted for nearly half of the TS DBS explantations in this cohort. There was no relationship to psychiatric comorbidities. Highlights: 5.6% of patients with Tourette syndrome DBS required lead removal. Infection accounted for almost half of all causes for DBS lead removal. There was no association between DBS lead removal and comorbidities. At least one patient asked for DBS lead removal despite great reduction in tics.